Linking herbivory and ecosystem services in urban forests. (February 2023) - Moreira, Xoaquín; Abdala-Roberts, Luis
Abstract: Urban forests provide important benefits for humans. Species interactions, in particular herbivory, can alter their function and ultimately threaten their ecosystem service provisioning. We call for research that identifies herbivory drivers in urban forests and tests for links between herbivory and forest services. Knowledge gained can inform management of urban ecosystems.